Pemberdayaan Anak Jalanan Berbasis Kesehatan, Spritual, dan Kemandirian Sosial - yessi harnani; Agus Alamsyah; Fitrianto Fitrianto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Street children are a real phenomenon part of life that causes complex problems, not only social problems but also health problems. The existence of street children in the city of Pekanbaru often makes people restless because they often make noise and disturb the surrounding community. The purpose of this service is to provide assistance and guidance to street children to live healthy and productive lives. This community service activity was carried out at the Pekanbaru City Shelter for 15 street children. The duration of the activity is 3 months. Partners in this activity are the Pekanbaru City Social and Funeral Service and Harapan Raya Health Center Pekanbaru City. The results of the activity are 1) Providing mental spiritual strengthening guidance, 2) Increasing knowledge of street children about adolescent reproductive health, the dangers of free sex, HIV AIDs and peer counselor training, 3) Facilitating VCT and STD examinations, 4) Providing special skills such as making organic fertilizers from household waste. The enthusiasm of street children to participate in this activity is quite high. This is evident from their seriousness in participating in all stages of this activity and it can be seen that there is an increase in the knowledge of street children both about religion, reproductive health, HIV AIDs and VCT test results which show that all street children are negative for HIV AIDs and none have sexually transmitted diseases ( STD).